A Quest to Nurture Creativity in Technology Classrooms: Are Physical Factors a Spanner in the Works? - Magolego, Maokanyane Patricia; Mtshali, Isaaac Thokozani; Manto, Ramaligela Sylvia (Research in Social Sciences and Technology- OpenED Network, 2024)
Nurturing creativity in Technology classrooms will, potentially, prepare learners for adaptability to the sweeping transformations that the new industrial revolutions portend and equip them to maximise the opportunities inherent in these revolutions. This study examined the effects of physical factors on the development of creativity in Grade 9 Technology classrooms. A qualitative research design was employed to purposively sample three Grade 9 Technology teachers to participate in this study. Open-ended questionnaires and non-participant observations were used as the methods of data collection for the study and the data were analysed thematically. The research findings show that creative pedagogy and the resultant development of creativity in the classroom, to a significant extent, are influenced by physical factors – class size and availability of Technology equipment. The study contributes to the body of knowledge by outlining how unfavourable physical conditions hinder the development of creativity skills in Technology classrooms, which is a core objective of the Curriculum Assessment Policy Statement (CAPS) guiding Technology education in South Africa. The study outlines the importance of a conducive learning environment to the quest to enhance learners’ creativity. Furthermore, the study recommends solutions to the paucity of resources for the enhancement of creativity in the Technology classrooms.